THE PROBLEM OF FINDING AN ADEQUATE EQUIVALENT IN TRANSLATION OF POLYSEMANTIC WORDS IN UZBEK AND FOREIGN LANGUAGES - Egamberdiyeva Khojiya Abdumavlon qizi (Western European Studies, 2026)
Interlingual interaction and exchange are becoming increasingly important in today's era of globalization. When learning and translating different languages, it is important to correctly understand and convey the underlying nature of linguistic phenomena. In this regard, one of the most complex problems encountered in the translation process is the correct and adequate transfer of polysemantic, i.e. words with multiple meanings, from one language to another. Each language has its own content system and semantic content, and the words in it cover different areas of meaning. Polysemantic words take on a more complex and multifaceted phenomenon in such a scope.
Keywords: Polysemantic word; Polysemantic wordPolysemantic word; Uzbek language